ACHIEVING COMPETITIVE ADVANTAGE THROUGH PRACTICING TQM TOOLS IN PHARMACEUTICALS COMPANY (Journal of Mechanical Engineering, 2014)
In order to survive in a competitive market, improving quality and productivity of Product or processis a must for any company. And in case of pharmaceutical industry, effective quality assurance policyimplementation is the most important goal. The main objective of this paper is to apply the Total QualityManagement (TQM) tools in a pharmaceutical company and prove its advantage. Here Control Chart,Fishbone diagram, EWMA were used and the control limits were improved. This activity resulted in moreperfect control limit recommendations which actually capable of reducing the material cost. The TQMperspective views quality as the pivotal purpose of the organization. Present review attempts to furnish a wideoverview of the TQM tools leading to quality improvement of Pharmaceuticals Company.DOI: http://dx.doi.org/10.3329/jme.v43i2.17834